Development of a skeletal oxidation mechanism for Fischer–Tropsch diesel surrogate based on decoupling method and particle swarm optimization. (December 2020) - Chen, Wenkai; Fang, Xiaoyuan; Zhu, Cheng; Qiao, Xinqi; Ju, Dehao
As an alternative liquid fuel, Fischer–Tropsch (FT) diesel has received significant attentions due to its characteristics of high efficiency and low emission. In this study, a surrogate fuel containing iso-hexadecane and n-dodecane with a mole ratio of 0.16:0.84 is formulated for real FT diesel by mimicking its combustion-related physicochemical properties. Mechanisms of these two components are developed based on decoupling methodology: skeletal sub-mechanisms describing iso-hexadecane and n-dodecane cracking process are constructed and combined with a reduced C0 –C4 core mechanism, and then the Arrhenius parameters of certain reactions are tuned by particle swarm optimization algorithm to improve prediction accuracy. The optimized mechanisms are validated against experimental results of ignition delays, species concentrations and laminar flame speeds for iso-hexadecane and n-dodecane, respectively. Finally, by merging all the sub-mechanisms mentioned above, a skeletal oxidation model for FT diesel surrogate including 73 species and 324 reactions is obtained and employed in 3D CFD simulations to validate the ignition behavior of FT diesel sprays in a constant-volume combustion vessel; the simulation results show good agreement with experimental data.